75.2k views
0 votes
3^3 * 3^2 * 3^1 * 3^0 * 3^−1 * 3^−2 =

2 Answers

6 votes

Greetings from Brasil...

In this problem we can use the potentiation property:

→ Multiplying powers of the same base, maintaining the base and adding the exponents, that is:

Mᵃ · Mᵇ = Mᵃ⁺ᵇ

Applying to the question

3³ · 3² · 3¹ · 3⁰ · 3⁻¹ · 3⁻² = 3⁽³ ⁺ ² ⁺ ¹ ⁺ ⁰ ⁺ ⁽⁻ ¹⁾ ⁺ ⁽⁻ ²⁾⁾ = 3³

27

3^3 * 3^2 * 3^1 * 3^0 * 3^−1 * 3^−2 =-example-1
User Mikey Mouse
by
5.4k points
3 votes

Answer:

27*9*3*1*1/3*1/9

729*1/3*1/9

729/27

27ans

User Alex Chugunov
by
5.0k points